Liquid chromatography-tandem mass spectrometry for the quantification of ripretinib and its metabolites DP-5439 in human plasma - Jiahui Lin; Jiahui Lin; Aiting Jiang; Juntao Zheng; Jingjing Wu; Hao Li; Hao Li; Shirong Cai; Yulong He; Xiao Chen; Guoping Zhong; Ke-Jing Tang; et al. (Frontiers in Pharmacology)
BackgroundRipretinib, a broad-spectrum tyrosine kinase inhibitor, has been approved for the treatment of advanced gastrointestinal stromal tumors in adult patients. Clinical studies have shown that higher in vivo exposure of ripretinib correlates with improved efficacy, highlighting the potential clinical significance of therapeutic drug monitoring. In this study, a simple and stable liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was attempted to be established and validated for pharmacokinetic studies of ripretinib and its metabolite DP-5439 and therapeutic drug monitoring in human plasma.MethodRipretinib and DP-5439 were separated by chromatography using a Thermofisher Hypersil GOLDTM C18 HPLC column. The mobile phase for gradient elution is composed of 0.1% formic acid in water and acetonitrile. Multiple reaction monitoring was implemented along with electrospray ionization positive mode for detection. The ion pairs of ripretinib, DP-5439 and internal standard D8-ripretinib were m/z 510.1→m/z 417, m/z 496.11→m/z 402.9 and m/z 518.15→m/z 420, respectively. Plasma samples from ripretinib-treated patients of our hospital were collected for pharmacokinetic analysis.ResultsRipretinib and DP-5439 demonstrated a strong linear relationship over 10–5,000 μg/L (R2 > 0.99). Accuracy, precision, specificity, recoveries, matrix effect, stability, and dilution effect were all validated and found to meet the required criteria. Following validation, the method was utilized to determine plasma samples from patients treated with ripretinib. The median steady-state trough concentrations (Cmin, range) were 398.50 (66.98 ∼ 1,458.91) μg/L for ripretinib and 654.74 (30.71 ∼ 1,522.48) μg/L for DP-5439, with a total median concentration of 1,129.46 (140.95 ∼ 2,981.39) μg/L in patients receiving ripretinib at 150 mg once daily. Meanwhile, using the established methods, the study conducted pharmacokinetics studies on four patients with ripretinib and DP-5439.ConclusionThis study developed and validated a robust LC-MS/MS method for determining ripretinib and its metabolite DP-5439 in human plasma. Furthermore, the practicality of this method in clinical sample analysis was demonstrated. This approach can serve as an effective tool for the pharmacokinetics analysis and therapeutic drug monitoring in patients treated with ripretinib.